2017
DOI: 10.30574/gscbps.2017.1.3.0052
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of typhoid fever in Bingham University

Abstract: Typhoid fever remains a major cause of enteric disease and a significant public health problem. The disease is said to be very prevalent in the developing countries, of which Nigeria is one. The aim of this study is to determine the prevalence of typhoid fever among Bingham University students. A total of 125 blood and stool samples were collected randomly from both male and female students of Bingham University. The blood samples were tested for salmonella antigen using Widal test while stool samples were cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…The prevalence of typhoid among people with tertiary education reported in this study is consistent with a study in Zimbabwe which recorded a prevalence of 6.2% for participants with tertiary education [38]. Findings in this study, however, are in contrast with an earlier study conducted in Nigeria which reported a seroprevalence of 75.2% among tertiary students [39]. The difference may be as a result of differences in the levels of hygiene existing in the different study sites [37].…”
Section: Risk Factors Associated With Igm/iggsupporting
confidence: 87%
“…The prevalence of typhoid among people with tertiary education reported in this study is consistent with a study in Zimbabwe which recorded a prevalence of 6.2% for participants with tertiary education [38]. Findings in this study, however, are in contrast with an earlier study conducted in Nigeria which reported a seroprevalence of 75.2% among tertiary students [39]. The difference may be as a result of differences in the levels of hygiene existing in the different study sites [37].…”
Section: Risk Factors Associated With Igm/iggsupporting
confidence: 87%
“…Moreover, known HIV and inpatients were included in other studies, which might increase the seroprevalence. Similarly, the seroprevalence in the present study was lower than a study done in Nigeria among university students [13] reporting 69.6%. This variation might be due to the difference among study participants where students from Nigeria were living in a single campus, which might allow the occurrence of high TF prevalence in a specific study period because of a common infection source.…”
Section: Biomed Research Internationalcontrasting
confidence: 79%
“…Though different laboratory test methods and clinical specimens are used, the prevalence of S. Typhi is variable among different countries in Africa [9] and among different geographical locations in Ethiopia [10]. Previous studies done showed a heterogeneous prevalence of S. Typhi in African countries ranging from 5%-69.6% [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, a high proportion (46%) of Salmonella bacteraemia in children under 12 years of age was found. Statistical significance association of typhoidal salmonellosis with age had been documented and with children at the high risk of salmonellosis [21,24,25,33,54]. HIV infection, malaria parasitaemia coinfection with typhoid [17,21] sickle cell anaemia [28] and gender among others are certain predisposing factors reported to influence occurrence of Salmonellaassociated diseases in this study.…”
Section: Discussionmentioning
confidence: 53%